2008
DOI: 10.1093/intimm/dxn021
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for the natural killer cell-mediated induction of IgG1 and IgG2a expression in B lymphocytes

Abstract: Upon interaction with resting B lymphocytes, IL-2-propagated NK cells can initiate the process of Ig constant region switch recombination (CSR) by inducing germ line transcripts for gamma2a (Igamma2a) as well as increased levels of mRNA for activation-induced cytidine deaminase enzyme. Whereas both these processes are necessary for CSR, they are not sufficient because the cells do not proceed to the expression of mature mRNA for gamma2a (VDJCgamma2a). In addition, NK cells can also upregulate mRNA for the T-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The Th2 cytokine bias in gzmA3B ko mice might have promoted this, as IL-4 promotes IgG1, but blocks class switching to IgG2b in response to LPS (24). NK cells, which were enhanced early in wt mice, could also have promoted IgG2c production in wt mice (25).…”
Section: Humoral Response By B Cellsmentioning
confidence: 99%
“…The Th2 cytokine bias in gzmA3B ko mice might have promoted this, as IL-4 promotes IgG1, but blocks class switching to IgG2b in response to LPS (24). NK cells, which were enhanced early in wt mice, could also have promoted IgG2c production in wt mice (25).…”
Section: Humoral Response By B Cellsmentioning
confidence: 99%
“…Crosslinking of CD48 on NK cells leads to aggregation of CD244 on the same cell, resulting in phosphorylation of tyrosine residues and subsequent activation of -cytokine production [6]. In vitro experiments utilizing interleukin (IL)-2-propagated NK cells have indicated that stimulation of B cells by NK cells requires the presence of CD48 on B cells and leads to interferon (IFN)-γ-independent activation of downstream exons of the immunoglobulin (Ig) locus as revealed by germline transcriptions [7,8]. However, this activation does not result in productive DNA recombination, leading to the expression of functional transcripts unless the cells are also stimulated via the B-cell receptor [8].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments utilizing interleukin (IL)-2-propagated NK cells have indicated that stimulation of B cells by NK cells requires the presence of CD48 on B cells and leads to interferon (IFN)-γ-independent activation of downstream exons of the immunoglobulin (Ig) locus as revealed by germline transcriptions [7,8]. However, this activation does not result in productive DNA recombination, leading to the expression of functional transcripts unless the cells are also stimulated via the B-cell receptor [8]. On mast cells, CD48 itself may have receptor activity as well [9].…”
Section: Introductionmentioning
confidence: 99%
“…Murine 2B4 (CD244), the first member of the SLAM family identified (3,4), is expressed on all NK cells and on some T cells (4,5). Whereas 2B4 functions mainly as an activating receptor on human NK cells, on murine NK cells 2B4 has been shown to exert both activating and inhibitory effects on the cytotoxic activity of NK cells (4,(6)(7)(8)(9)(10). Unlike most of the other SLAM family members that have self-ligands, 2B4 has a unique ligand, CD48 (6).…”
mentioning
confidence: 99%
“…Using this approach, we have shown previously that some subsets of B cells are effective inducers of NK cell activation via the CD48-2B4 interaction (7). In addition, 2B4 can also function as a ligand to activate B cells via CD48, although CD2 is a more effective stimulator in this case (8). In an effort to understand how CD48 activates NK cells, we have extensively analyzed the effect of ligation of CD48 by anti-CD48 on NK cells.…”
mentioning
confidence: 99%